Producción y usos de piedras moleras en Puente Genil (Córdoba) durante la segunda mitad del siglo xvi - Ricardo Córdoba de la Llave (Mélanges de la Casa de Velázquez, 2019)
The find of an exceptional set of notarial documents from Puente Genil, conserved in the Provincial Historical Archive of Cordoba and dated between 1566 and 1594, has allowed a deeper knowledge of the exploration of millstone quarries located around of this town during the second half of the sixteenth century. The features of the work are approached from a technical (types and location of the quarries, extraction systems of the stones, type of grinding stones obtained) and human (property of the quarries, workers organization, systems used for transport, territorial scope of use and economic cost of molars) point of view, deepening the understanding of this activity during one of the most intense periods of exploitation in its history.